2008
DOI: 10.1097/qai.0b013e31815e4011
|View full text |Cite
|
Sign up to set email alerts
|

HIV Incidence Among Men Diagnosed With Early Syphilis in Atlanta, San Francisco, and Los Angeles, 2004 to 2005

Abstract: We found high HIV incidence among a high-risk population of US men diagnosed with P&S syphilis in STD clinics in Atlanta, San Francisco, and Los Angeles. Intensive integrated HIV/STD prevention programs are needed for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 34 publications
2
56
0
Order By: Relevance
“…[14][15][16] Although early clinical results from these studies appear promising and reported rates of surgeon satisfaction are high, to date, little data have been published on the quality and reliability of material that has been precut by tissue banks. 17 The aim of the present study was to address this issue by reviewing the characteristics and quality of a large number of EK donor tissues processed using an automated microkeratome method by a large, centralized eye bank over a 1-year period.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Although early clinical results from these studies appear promising and reported rates of surgeon satisfaction are high, to date, little data have been published on the quality and reliability of material that has been precut by tissue banks. 17 The aim of the present study was to address this issue by reviewing the characteristics and quality of a large number of EK donor tissues processed using an automated microkeratome method by a large, centralized eye bank over a 1-year period.…”
Section: Introductionmentioning
confidence: 99%
“…One study at the University of Iowa calculated that running the OR at their institution costs an average of $35 per minute, which depending on the experience level of the surgeon, could make the transplant surgery considerably more expensive. 5 Other financial considerations include the cost of purchasing and maintaining the cutting equipment to specifications. The benefits of using precut tissue from an eye bank extend beyond potential cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…Although some surgeons still prefer to cut their own graft tissue from donor corneas while in the operating room (OR), a growing body of literature has shown that precut corneas yield similar endothelial cell loss, visual and refractive outcomes, and dislocation rates compared with surgeon-cut tissue. 3,4 In addition, eye bank-cut tissue offers significant advantages including shorter OR times 5 and virtually no risk of tissue wastage due to unsuccessful sectioning by the surgeon. The purpose of this study was to evaluate the accuracy of eye bank-prepared precut donor corneas over time by comparing cut-failure rates and corneal thickness measurements obtained from 2511 specimens in 2010 and 2013 from a single large eye bank.…”
mentioning
confidence: 99%
“…This is in agreement with studies that have previously shown that surgeon experience directly correlates with surgical success. 10,12,13 Additionally, graft failure is highest with a surgeon's initial cases. Price et al 15 reported 7 cases of primary graft failures, defined as a graft that failed to clear after 2 weeks, of which 6 occurred in the first 100 cases and only 1 occurred in the second 100 cases.…”
Section: Surgeon Experiencementioning
confidence: 99%
“…As published in previous studies, no demonstrable difference in complication rates exists between the utilization of precut tissue and surgeon-cut tissue. 10,[18][19][20][21] …”
Section: Patient and Tissue Characteristicsmentioning
confidence: 99%